2011
DOI: 10.1063/1.3551628
|View full text |Cite
|
Sign up to set email alerts
|

ZnO homojunction photodiodes based on Sb-doped p-type nanowire array and n-type film for ultraviolet detection

Abstract: The cooling effect on structural, electrical, and optical properties of epitaxial a-plane ZnO:Al on r-plane sapphire grown by pulsed laser deposition Appl. Phys. Lett. 101, 151907 (2012) Multiphonon scattering and photoluminescence of two dimensional ZnS nanosheets grown within Na-4 mica J. Appl. Phys. 112, 074321 (2012) Growth study of nonpolar Zn1−xMgxO epitaxial films on a-plane bulk ZnO by plasma-assisted molecular beam epitaxy Appl. Phys. Lett. 101, 122106 (2012) Mechanical and electrical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 23 publications
(19 reference statements)
1
67
0
Order By: Relevance
“…Clearly, the Sbdoped ZnO nanorod exhibited p-type character. The hole concentration and the mobility in the nanorod, derived using the cylinder-on-an-infinite-plate model, 6 were calculated to be 3.59 Â 10 17 cm À3 and 0.0475 cm 2 V À1 s À1 , respectively. These values are close to those of p-type Sb-doped ZnO fabricated by hydrothermal methods.…”
mentioning
confidence: 99%
“…Clearly, the Sbdoped ZnO nanorod exhibited p-type character. The hole concentration and the mobility in the nanorod, derived using the cylinder-on-an-infinite-plate model, 6 were calculated to be 3.59 Â 10 17 cm À3 and 0.0475 cm 2 V À1 s À1 , respectively. These values are close to those of p-type Sb-doped ZnO fabricated by hydrothermal methods.…”
mentioning
confidence: 99%
“…The efficiency of the dopant atoms depends on difference between their ionic radius and the ionic radius of host atoms (zinc or oxygen) [18]. Yakuphanoglu et al [19] have reported photoluminescence and optical properties of nanostructure Ni-doped ZnO thin films prepared by sol-gel spin coating technique.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of 1D ZnO nanostructure into highly ordered hierarchical architectures with morphology uniformity and narrow size distribution has attracted much attention owing to its promising applications to nanodevices, such as field emission transistors [5] and solar cells [6]. There have been many reports about the physical and chemical methods to fabricate ordered hierarchical heterostructure based on 1D ZnO nanostructure, including metal organic chemical vapor deposition (MOCVD), thermal vapor deposition, pulsed laser deposition, molecular beam epitaxy, electron beam evaporation, spray pyrolysis, electrochemical deposition, and hydrothermal synthesis [7][8][9][10][11][12][13][14][15]. Among them, hydrothermal process is a low cost and large scale method.…”
Section: Introductionmentioning
confidence: 99%